Computer assisted learning vs. conventional teaching in experimental Pharmacology: perception of second year medical students - Sane, Rohit M.; Jadhav, Pradeep R. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The main pool of pharmacology practical teaching is formed by the use and demonstration of animal experiments. Animals have been used to demonstrate the effect of various drugs in experimental pharmacology classes, in the lab. The practical sessions in pharmacology training involving animal experiments are still taught by traditional teaching methods. Rapid development of information technology has led to newer trends in teaching and learning using Computer Assisted Learning (CAL). Keeping it in mind we decided to undertake this study to assess the perception of CAL in 2nd year MBBS students over conventional teaching in experimental pharmacology. Methods: This was an observational, questionnaire-based study. A total of hundred undergraduate MBBS (2nd year) students participated. Participants were first demonstrated an animal experiment by conventional teaching method followed by the same animal experiment demonstration on CAL. Students’ feedback was recorded on a questionnaire and analyzed. Results: The mean age of the participants was 19.88±1.28 years. The study overall observed that 62% preferred CAL to conventional (38%). Majority of the participants’ thought CAL (63%) helps to understand better over conventional (28%) and that CAL (63%) is time independent over conventional (28%). More than 85% felt that CAL was more explanatory and provided a better learning experience. Conclusions: Students preferred CAL to conventional teaching, in experimental pharmacology. It also provided insight on perception and experience of students towards CAL for experimental pharmacology. However, further studies are warranted to assess the knowledge, cognitive and psychomotor skills of students.